Enhancement of Laser-Induced Breakdown Spectroscopy (LIBS) Sensitivity Using Electric Fields: A Study on Non-Metal Samples - Tanra, Ivan; Limanto, Agus; Hadiyanto, Marvin Yonathan; Karnadi, Indra (Journal of Physics and Its Applications, 2025)
Laser-induced breakdown spectroscopy (LIBS) has proven to be a versatile and effective technique for elemental analysis across a variety of fields, including geology, archaeology, materials science, nuclear power, and medicine. This study focuses on the application of an external electric field to enhance the performance of LIBS, specifically for non-metal samples such as black coral. By introducing an electric field and varying laser energy levels, the effects on plasma generation and emission intensities were investigated. The experimental results demonstrate that applying an electric field significantly enhances spectral intensity, with notable improvements in the Carbon (C I) emission line at 247.8 nm. The enhancement was observed to be nonlinear, with significant increases only when the electric field strength exceeded 200 V/cm. Laser energy was also found to play a critical role, with carbon signals only detectable at energies above 20 mJ, and optimal results achieved at 50 mJ. These findings highlight the combined effect of laser energy and electric field strength in enhancing LIBS sensitivity, particularly for detecting trace elements in organic samples. This approach offers a simple, efficient, and effective method to improve LIBS performance, with potential applications in fields such as fossil age determination and other analytical studies requiring high sensitivity.